PENERAPAN PENDEKATAN PENGAJARAN TERBALIK (RECIPROCAL TEACHING) UNTUK MENINGKATKAN KEMANDIRIAN BELAJAR BIOLOGI SISWA KELAS VII-G SMP N 5 KARANGANYAR TAHUN PELAJARAN 2010/ 2011 - Yunita, Yesie Erma; Santosa, Slamet; Ariyanto, Joko (P Biologi FKIP UNS Surakarta, 2011)
ABSTRACT ? The objective of this study is to improve student independence in learning biology by implementing Inverted Teaching Approach (Reciprocal Teaching) on Environmental Management material. This research is a classroom action research. This research was conducted in two cycles. Each cycle consisted of planning, implementation of the action,observation, and reflection. The subjects of the study were VII-G class students of SMP Negeri 5 Karanganyar in the academic year of 2010/2011. The number of the students was 32. The technique and instrumen of collectiing data were questionnaire, observation, and interviews. The technique of analyzing data was descriptive analysis techniques. Triangulation technique was used in data validation. The results proved that by implementing Inverted Teaching Approach (Reciprocal Teaching) students' independence in learning biology enhanced. It is based on the results of questionnaires, observations and interviews. The questionnaire of students? learning independence showed that the mean percentage of students? achievement in each indicator in pre-cycle, cycle I, and cycle II was 67.97%, 72.55%, and 77.58% respectively. The observation of students? learning independence showed that the mean percentage of students? achievement in each indicator in pre-cycle, cycle I, and cycle II was 39.68%, 67.5%, and 80.62% respectively. It can be concluded that the implementation of Inverted Teaching Approach (Reciprocal Teaching) can enhance students learning independence. Keywords: Inverted Teaching Approach( Reciprocal Teaching), Learning Independence, Biology Learning